Disiplin Kerja Guru Dalam Proses Belajar Mengajar Di SMP It Istiqomah Bengkulu - Riyanto, Agus (AHSANTA JURNAL PENDIDIKAN, 2019)
Teachers at school have a big burden in creating generations of students to compete in the current era of 4.0. Teachers work discipline that will both accelerate the achievement ofeducational goals, and lack discipline will hamper the achievement of educational goals.Based on observations at SMP IT Istiqomah Bengkulu there were still found teachers who carried out their duties with low discipline. This type of research is quantitative, usingdescriptive analysis and data collection methods using questionnaires, with a sample of 30 people. The results of the study showed that the lecturers' employment was very goodcategory (4.58). Suggestions, lecturers should maintain discipline.